Spatial and temporal distribution of metals in suspended particulate matter of the Kali estuary, India. (5th September 2017) - Suja, S.; Kessarkar, Pratima M.; Fernandes, Lina L.; Kurian, Siby; Tomer, Arti
Abstract: Major (Al, Fe, Mn, Ti, Mg) and trace (Cu, Zn, Pb, Cr, Ni, Co, Zr, Rb, Sr, Ba, Li, Be, Sc, V, Ga, Nb, Mo, Sn, Sb, Cs, Hf, Ta, Bi, Th, U) elements and particulate organic carbon (POC) concentrations in surface suspended particulate matter (SPM) of the Kali estuary, (central west coast of India) were studied during the pre-monsoon, monsoon and post monsoon seasons to infer estuarine processes, source of SPM and Geoaccumulation Index (Igeo) assigned pollutionIgeo levels. Distribution of SPM indicates the presence of the estuarine turbidity maximum (ETM) during all three seasons near the river mouth and a second ETM during the post monsoon time in the upstream associated with salinities gradient. The SPM during the monsoon is finer grained (avg. 53 μm), characterized by uniformly low normalized elemental concentration, whereas the post and pre monsoon are characterized by high normalized elemental concentration with coarser grain size (avg. 202 μm and 173 μm respectively) with highest ratios in the upstream estuary. The elemental composition and principal component analysis for the upstream estuary SPM support more contribution from the upstream catchment area rocks during the monsoon season; there is additional contribution from the downstream catchment area during the pre and post monsoon period due to the tidal effect. The Kali estuarine SPM has higher Al, Fe, Mn, Ti, Mg, Ni, Co, Ba, Li and V with respect to Average World River SPM (WRSPM). Igeo values for the SPM indicate Kali Estuary to be severely enriched with Mn and moderately enriched with Cu, Zn, Ni, Co, U and Mo in the upstream estuary during pre and post monsoon seasons. Seasonal changes in salinity gradient (reduced freshwater flow due to closing of the dam gates), reduced velocity at meandering region of the estuary and POC of 1.6–2.3% resulted in co-precipitation of trace elements that were further fortified by flocculation and coagulation throughout the water column resulting in metal trapping in the upstream region. Highlights: Estuarine turbidity maximum (ETM) is present near mouth throughout the year. Second ETM is observed in the upstream estuary during the post monsoon season. The grain size and composition of the SPM is observed to change with seasons. Fine grained SPM is dominantly sourced from rocks in the catchment area. Coarse grained upstream SPM is result of co-precipitation/re-suspension.